2010
DOI: 10.1111/j.1752-9824.2010.01047.x
|View full text |Cite
|
Sign up to set email alerts
|

The experience of parenting children with chronic health conditions: a new reality

Abstract: The experience of parenting children with chronic health conditions: a new reality Aim. This study was undertaken to synthesise recent qualitative literature in the years 2000 to 2009, exploring the phenomenon of parents' experiences of parenting a child with one or more chronic health conditions. Background. The experience of parenting children with chronic health conditions has been predominantly studied by examining the effects of specific illnesses such as sickle cell anaemia and cystic fibrosis. While the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
56
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 32 publications
2
56
1
Order By: Relevance
“…behavioral or emotional difficulties), and neglects the distress experienced by many parents. Parent distress interferes with their ability to assimilate new information at the point of diagnosis; subsequently, parents report a lack of information or misinformation and distrust for healthcare professionals (Kepreotes et al 2010). The risk is an increased chance of failure in condition management.…”
mentioning
confidence: 99%
“…behavioral or emotional difficulties), and neglects the distress experienced by many parents. Parent distress interferes with their ability to assimilate new information at the point of diagnosis; subsequently, parents report a lack of information or misinformation and distrust for healthcare professionals (Kepreotes et al 2010). The risk is an increased chance of failure in condition management.…”
mentioning
confidence: 99%
“…A focus on the manifestations of expertise displayed by health professionals and by parents of a child with a chronic disease provides an opportunity to re-examine expert lay knowledge in the context of the specialty-medical consultation. Kepreotes and Keatinge (2010) conducted a metasynthesis of qualitative literature published between 2000 and 2009 that explored parents' experiences of parenting a child with a chronic health condition. Key findings describe parents' ongoing grief relating to diagnosis and beyond, lack of information and the inadequacy of relationships with professionals.…”
mentioning
confidence: 99%
“…While caring for a child with a chronic health condition demands much attention and time of the parenting role, it was also found be a most overwhelming task, resulting in fatigue, role strain, and depression. Characteristics such as grief, fear, vigilance, isolation, confusion, a fragile sense of control, advocacy, and uncertainty were described in two metasyntheses of parenting a child across a spectrum of chronic health conditions (J. S. Coffey, 2006;Kepreotes, Keatinge, & Stone, 2010). In addition, these studies reported more covert findings that many families eventually defined as a new normal.…”
Section: Parenting a Child With Cfmentioning
confidence: 99%
“…In part, findings reflect inconsistent definitions of terminology, roles, functions, and contexts (Gage, Everett, & Bullock, 2006;Nicholl & Begley, 2012). Studies have explored parenting a child with a chronic health condition through a general perspective on chronic illness (J. S. Coffey, 2006;Kepreotes et al, 2010;Ray, 2002), disease-specific perspectives (Carpenter & Narsavage, 2004;Cronin, 2004;Moola, 2012), and other factors such as coping and adjustment (Rehm, 2000), family function (Knafl & Deatrick, 1986;McClellan & Cohen, 2007); sleep (Meltzer & Mindell, 2006;Yilmaz et al, 2008), and depression (Besier et al, 2011;Smith, Modi, Quittner, & Wood, 2010). Parenting a child with a chronic health condition has also provoked parenting studies, particularly the traditional maternal role as primary caregivers.…”
Section: Parenting a Child With Cfmentioning
confidence: 99%
See 1 more Smart Citation